Potential use of Wolffia globosa powder supplementation on in vitro rumen fermentation characteristics, nutrient degradability, microbial population, and methane mitigation - Uswatun Muslykhah; Chaichana Suriyapha; Srisan Phupaboon; Sunisa Pongsub; Maharach Matra; Gamonmas Dagaew; Sukruthai Sommai; Metha Wanapat (Scientific Reports)
Abstract This study examined the potential of duckweed powder (DWP) on in vitro fermentation characteristics, nutrient degradability, microbial change, and methane (CH4) production using in vitrostudy technique. This investigation used a 2 × 6 factorial arrangement in a completely randomized design (CRD) by different roughage-to-concentrate (R: C) ratios of 60:40 and 40:60 combined with DWP supplementation levels at 0, 2, 4, 6, 8, and 10% of the total dry matter (DM) substrate, respectively. There was an interaction effect by R: C ratios combined with DWP supplementations that changed gas production rate, pH value (4 h; h), volatile fatty acid (VFA) (8 h), in vitro dry matter degradability (IVDMD) at 12 h, and concentration of ammonium nitrogen (NH3-N) (p < 0.05). Furthermore, the R: C ratio (40:60) significantly decreased CH4 production (4 and 8 h), pH (8 h), and Ruminococcus albus (8 h) (p < 0.05), while it significantly increased total VFA (8 h), and nutrient degradability (p < 0.05). DWP 4% significantly increased to the highest of gas production, improved nutrient degradability (IVDMD at 24 h and in vitro organic matter degradability; IVOMD at 12 h), whereas significantly decreased Methanobacteriales (8 h) and CH4 production. DWP 4% has potential as a ruminant feed additive for reducing Methanobacteriales and CH4 emission and enhancing rumen fermentation.